Peran Moderasi Non Performing Financing Terhadap Pembiayaan Mudharabah, Musyarakah, Dan Profit Sharing Ratio Pada Profitabilitas Bank Umum Syariah - Rekno Sawiji Lestari; Saiful Anwar (LPPM ISNJ Bengkalis, 2021)
The purpose of this study was to show the effect of mudharabah, musyarakah, and profit-sharing ratios on profitability with non-performing financing as moderating variables in Islamic commercial banks. This research method was designed using a quantitative approach. The sample used in this study was nine banks with a sampling technique using purposive sampling. The analytical method used is multiple linear regression. The results showed that mudharabah financing had a positive and significant effect on profitability, musyarakah financing and profit-sharing ratio did not affect profitability. Non-performing financing can moderate the effect of mudharabah financing and profit-sharing ratio but cannot moderate the effect of musyarakah financing on profitability. This research practically develops financing that can increase profitability and reduce non-performing financing to reduce losses for Islamic Commercial Banks.